Screening IVA Test Effort to Increase Intention for Early Detection Cancer Cervix in Panyabungan, Mandailing Natal - Ayu Ulfah Nur Lubis; Wahyuni Harahap; Kiki Khoiriyani; Doriani Harahap (International Journal of Public Health Excellence (IJPHE), 2026)
Cervical cancer remains one of the leading causes of death among women in Indonesia, largely due to delays in treatment due to lack of knowledge of early detection. IVA (Visual Inspection with Acetic Acid) examination is a simple, affordable, and effective screening method to recognize early symptoms of cervical cancer, especially in communities with limited access to advanced health facilities. This service activity aims to provide comprehensive education on cervical Cancer prevention efforts through a promotive and preventive approach based on VIA. Counseling is conducted to productive-aged women with interactive methods that include material delivery, group discussions, and simulation of general examination procedures. The results showed an increase in participants' understanding of the importance of routine screening, recognition of early symptoms, and preventive measures that can be taken independently. This program is expected to be able to foster public awareness of the importance of early detection and become part of a strategy to empower women in maintaining their reproductive health in a sustainable manne